Profil Asam Amino Penstimulasi Sekresi Insulin dalam Ekstrak Sesudah Pemisahan Protein Kecambah Kacang-Kacangan Lokal - Bayu Kanetro; Astuti Setyowati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
There are many local legumes in Indonesia that are potential to substitute soybean as functional food. Seed germination of legumes increased protease activity that could hydrolize protein, hence the extract of legumes sprout after removal of macromolecule protein contained small peptides dan free amino acids. The aims of this research were to determine the best local legume (winged bean, velvet bean, or cowpea) sprout based on its profile of amino acid for stimulation of insulin secretion such as Leucine (Leu), Arginine (Arg), Alanine (Ala), Phenylalanine (Phe), Isoleucine (Ile), and Lycine (Lys) in the extract after removal of macromolecule protein. Legume seeds were germinated, dried, and milled become the flour. The extracts of legume sprouts were prepared by mixing the flour and aquadest, centrifugated, and removed of the protein by precipitation at pH isoelectris. The extracts after removal of the macromolecule protein were analyzed for the total solid, soluble protein, and the profile of amino acid for stimulation of insulin secretion by HPLC. The result of this research showed that the extract of legumes sprout contained soluble protein and amino acid for stimulation of insulin secretion. The content of amino acids in the extract after removal of the protein of winged bean, velvet bean, cowpea sprouts and soybean seed as a control were 142,00; 206,40; 183,00; and 129,00 µg/ml for the Ala; 627,00; 1604,80; 524,00; and 422,40 µg/ml for the Arg; 136,00; 340,00; 124,20; and 119,40 µg/ml for the Phe; 122,80; 322,80; 104,60; and 100,40 µg/ml for the Ile; 190,80; 440,80; 136,40; and 168,00 µg/ml for the Leu; 340,40; 748,40; 177,00; and 256,40 µg/ml for the Lys respectively. Based on the data, the velvet bean was chosen as the best legume due to the contain of amino acids for stimulation of insulin secretion was higher than the other legumes.ABSTRAKIndonesia memiliki kacang-kacangan lokal yang berpotensi menggatikan kedelai sebagai pangan fungsional. Perkecambahan kacang-kacangan meningkatkan aktiviyas protease yang dapat menghidrolisis protein, sehingga ekstrak kecambah kacang-kacangan sesudah pemisahan protein mengandung peptida sederhana dan asam amino bebas. Tujuan penelitian ini adalah untuk menentukan jenis kecambah kacang-kacangan lokal ( kecipir, kara benguk, atau tunggak) terbaik berdasarkan profil asam amino penstimulasi sekresi insulin, yaitu kandungan alanin (Ala), arginin (Arg), fenilalanin (Phe), isoleusin (Ile), leusin (Leu) dan lisin (Lys).Biji kacang-kacangan dikecambahkan, dikeringkan dan digiling sehingga menjadi tepung. Ekstrak kecambah kacang-kacangan diperoleh dengan cara pencampuran tepung dan aquades, sentrifugasi dan pengendapan protein pada pH isoelektris. Ekstrak kecambah kacang-kacangan sesudah pemisahan makromolekul protein dianalisis kadar padatan total, protein terlarut dan profil asam amino penstimulai sekresi insulin menggunakan HPLC. Hasil penelitian menunjukkan bahwa ekstrak kecambah kacang-kacangan mengandung protein terlarut dan asam amino penstimulasi sekresi insulin. Kandungan asam amino tersebut dalam ekstrak kecambah kecipir, kara benguk, tunggak, dan biji kedelai sebagai kontrol berturut-turut mulai dari kadar Ala yaitu 142,00; 206,40; 183,00; dan 129,00µg/ml; kadar Arg yaitu 627,00; 1604,80; 524,00; dan 422,40µg/ml; kadar Phe yaitu 136,00; 340,00; 124,20; dan 119,40µg/ml; kadar Ile yaitu 122,80; 322,80; 104,60; dan 100,40µg/ml; kadar Leu yaitu 190,80; 440,80; 136,40; dan 168,00µg/ml; kadar Lys yaitu 340,40; 748,40; 177,00; dan 256,40µg/ml ekstrak. Berdasarkan data tersebut, kacang kara benguk dipilih sebagai kacang-kacangan terbaik karena kadar asam-asam amino penstimulasi sekresi insulinnya lebih tinggi dibandingkan jenis kacang-kacangan yang lain.